2011
DOI: 10.1007/s12274-011-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

Binder-free activated carbon/carbon nanotube paper electrodes for use in supercapacitors

Abstract: Novel inexpensive, light, flexible, and even rollup or wearable devices are required for multi-functional portable electronics and developing new versatile and flexible electrode materials as alternatives to the materials used in contemporary batteries and supercapacitors is a key challenge. Here, binder-free activated carbon (AC)/carbon nanotube (CNT) paper electrodes for use in advanced supercapacitors have been fabricated based on low-cost, industrial-grade aligned CNTs. By a two-step shearing strategy, ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(72 citation statements)
references
References 61 publications
1
70
1
Order By: Relevance
“…Binder-free activated carbon/carbon nanotube paper electrodes for use in supercapacitors were fabricated in [78]. The specific capacitance reached a maximum value of 267.6 F/g for a loading of 5 wt % of carbon nanotubes.…”
Section: Nanostructured Carbon -Based Compositesmentioning
confidence: 99%
“…Binder-free activated carbon/carbon nanotube paper electrodes for use in supercapacitors were fabricated in [78]. The specific capacitance reached a maximum value of 267.6 F/g for a loading of 5 wt % of carbon nanotubes.…”
Section: Nanostructured Carbon -Based Compositesmentioning
confidence: 99%
“…The development of such devices implies higher requirements on their battery systems, in which flexibility of the electrodes is essential to enable their bendable features [1][2][3]. Typically, the conventional lithium-ion batteries (LIBs) have electrodes containing metal substrates, which are coated with a mixture of an active material, an electrical conductor, a binder, and a solvent [ 4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by vacuum filtration of the stable suspension containing both CNTs and AC particles. [15,38,66] Experimental results also demonstrated that the flexible composite electrodes have much better performance compared with other electrodes made with traditional approaches. Flexible and binder-free CNTs/AC electrodes containing 95 wt% of AC were able to reach specific capacitance of 268 F/g at 200 mV/s in 6 M KOH.…”
Section: Flexible Electrodes Based On Composite Carbonmentioning
confidence: 89%
“…Energy density of 22.5 Wh/kg and power density of 7.3 kW/kg, along with remarkable stability of 97.5% retention for 5,000 cycles were also demonstrated. [38] …”
Section: Flexible Electrodes Based On Composite Carbonmentioning
confidence: 99%